Reformulasi al-Qawā’id al-Uṣūliyyah al-Tashrī’iyyah dalam Pengembangan Fiqih Kontemporer - Nur, Iffatin; Muttaqin, M. Ngizzul; Wakhid, Ali Abdul (Universitas Islam Negeri Raden Intan Lampung, 2020)
As a first step in extracting Islamic law, namely through the study of texts, qawa'id al-uṣūliyyah al-tasyri’iyah in this way has an important position in the discourse of studying Islamic law. Unfortunately, in today's situation, al-qawā‘id al-uṣūliyyah al-tashrī'iyyah seems to be ruled out. This position is taken by ijtihād models based on a progressive approach rather than an approach to the text. This study is a discourse analysis using a qualitative method with a normative approach. In this study, the author examines the concept of al-qawā‘id al-uṣūliyyah al-tashrī'iyyah which is then formulated in several issues and problems of contemporary Islamic law. The findings in this study indicate that: first, the al-qawā'id al-uṣūliyyah al-tashrī'iyyah model in determining and establishing Islamic law places more emphasis on the substance of fundamental values in Islamic law, second, reformulation of al-qawā'id al -uṣūliyyah al-tashrī'iyyah in the settlement of contemporary Islamic law puts forward the protection of mafsadat rather than the taking of maṣlaḥah.